2015
DOI: 10.1021/acs.jchemed.5b00424
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Chemical Information Instruction into the Chemistry Curriculum on Borrowed Time: A Multiyear Case Study of a Capstone Research Report for Organic Chemistry

Abstract: To develop information literacy skills in chemistry and biochemistry majors at a primarily undergraduate institution, a multiyear collaboration between chemistry faculty and librarians has resulted in the establishment of a semester-long capstone project for Organic Chemistry II. Information literacy skills were instilled via a progressive research report, supported by a comprehensive modular virtual tutorial catered toward Rider University students, on the efficient use of SciFinder and related tasks for sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…Although there are more biochemistry projects each year, this group meeting time demonstrates the chemical foundation in both. The biochemistry lab content is largely based on an advanced biochemistry laboratory course developed by Linda Roberts at CSU Sacramento, and the chemistry projects are based on chemical studies published in this and other journals. During Spring Break of 2020, halfway through the semester, it became clear that, due to COVID-19, students would not return to the lab to complete their semester project and that the faculty would have to provide an alternative, remote format to conclude the capstone experience. This paper will detail the original class format, describe how the class structure changed when SSU was directed to pivot, and comment on what worked well and what could be improved to guide our chemical community should these types of modified capstone learning experiences have to be repeated or institutionalized.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are more biochemistry projects each year, this group meeting time demonstrates the chemical foundation in both. The biochemistry lab content is largely based on an advanced biochemistry laboratory course developed by Linda Roberts at CSU Sacramento, and the chemistry projects are based on chemical studies published in this and other journals. During Spring Break of 2020, halfway through the semester, it became clear that, due to COVID-19, students would not return to the lab to complete their semester project and that the faculty would have to provide an alternative, remote format to conclude the capstone experience. This paper will detail the original class format, describe how the class structure changed when SSU was directed to pivot, and comment on what worked well and what could be improved to guide our chemical community should these types of modified capstone learning experiences have to be repeated or institutionalized.…”
Section: Introductionmentioning
confidence: 99%
“…2 Three general instructional strategies are reported that integrate IL skills in the chemistry curriculum: (1) throughout the undergraduate and graduate chemistry curriculum; 3−7 (2) in IL-specific coursework; 8−11 (3) and in online modules. 12,13 The acquisition of disciplinary expertise of transferable skills, like information literacy, writing, and oral communication, should be situated or located within the context of the disciplines. This position is based on the argument that opportunities are needed to "facilitate the socialization of students into the information practices that are characteristic of the various "tribes" in which they aspire to belong" and where information literacy is "central to disciplinary expertise".…”
Section: ■ Introductionmentioning
confidence: 99%
“…At the undergraduate level, there is a recognized need for focusing on developing these information literacy (IL) skills as evidenced by recent, pointed attention on chemical information literacy in the published literature . Three general instructional strategies are reported that integrate IL skills in the chemistry curriculum: (1) throughout the undergraduate and graduate chemistry curriculum; (2) in IL-specific coursework; (3) and in online modules. , …”
Section: Introductionmentioning
confidence: 99%
“…These instructors introduced tasks employing lower levels of writing complexity before progressing to higher-level aspects, often following Rosenthal’s hierarchy. This implementation has often been categorized as a “progressive” writing strategy, and though this term has been often been utilized, a specific definition has seemingly not been agreed upon. ,, Here I propose to specifically define a “stepwise” writing strategy as the graduated progression over time from less-complex to more-complex writing tasks based on Rosenthal’s hierarchy. It is therefore a type of progressive strategy and shares many similarities with “scaffolding”. , …”
Section: Introductionmentioning
confidence: 99%